A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMA AL-FITYAH PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Dewi, Surya; Azhar, Fadly; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study is to find out the ability of the first year students of SMA Al-Fityah Pekanbaru in writing descriptive texts. The population of this research was all of the first year students of SMA Al-Fityah Pekanbaru which consist of 28 students. All students of the first grade were participated in this study. The instrument was writing test in form of a picture, that was a picture of a cat. The aspects that were evaluated are content, organization, grammar, vocabulary, and mechanic. To analyze the data, the mean scores were calculated and the level of ability of the students was identified by using the classification of ability level by Harris (1974). The result showed that the ability of the first year students of SMA Al-Fityah Pekanbaru in writing descriptive texts was at good level with mean score 78.68. Therefore, it can be concluded that most of the students were able to write descriptive texts. However, students are expected to start the writing in a first draft. In this step, they are free to express their ideas to write and free to construct sentences. Yet, in the final draft they are required to be careful to construct sentences with correct grammar and to write correct spelling, punctuation and capitalization.Key Words: Ability, Writing, Descriptive Texts